Financial inclusion and disparity: A case of India - Meenakshi Rajeev (International Labour Organization (ILO), 2015)
This paper highlights the inequality in financial penetration and usage in India, based on macro level data, and shows how certain regions, such as the Northeastern or Eastern of the country need special attention by the policy makers. Credit schemes need to be formalized so that the weaker regions and socially disadvantaged sections, especially in the lower income categories, receive better access to formal credit. Based on the analysis of unit record (household level) data from the National Sample Survey Organisation (NSSO), the gender-wise inequality is also considered persistent, particularly regarding access to credit. This paper argues that some of these selected groups need special attention by the formal credit institutions. The mere opening of a bank account in the name of financial inclusion for these sections is not sufficient. One needs to facilitate them in such a manner that their relation with banks becomes a sustainable one.
Keywords: 330; financial policy; credit system; regional disparity; equal rights; sex discrimination; household income; rural area; urban area; survey; India